MONEY SUPPLY ROLE IN ECONOMIC AND INDUSTRIAL GROWTH: THE CASE OF JORDAN (1990-2010) - Jaber Mohammed Al-Bdour; Abdul Ghafoor Ahmad (European Scientific Journal, ESJ, 2012)
Economic theorists from David Hume to Keynes and new Monetarists are all emphasize monetary policy measures to induce economic growth and industrial development. This policy is also used to cure sharp inflation and economic crises. The most two popular monetary measures, used by most countries are money supply and the interest rate. Were these measures used effectively in Jordan? Were they used as inducers or did they just grow parallel and coincided with the achieved economic growth and production in Jordan during the first decade of this century, at a time when the world faces economic and financial crises? The core and the essence of this empirical paper will be to answer these questions with the focus on the money supply role in economic growth.Regression model with lag one year was used in this paper. The purpose of this type of models is to evaluate whether money supply was inducer or grew parallel to economic growth and growth in the industrial sector. For comparisons, two periods were studied. Each period is for a decade. The first period covered the years 1990 to 2000, and the second period covered the years 2001 to 2010.It is concluded that in both periods money supply in Jordan was not used as an inducer to the growth of the economy neither used as an inducer to the growth in the industrial sector.